A new species of anole related to Anolis altae from Volcán Tenorio, Costa Rica (Reptilia, Squamata, Polychrotidae) - Köhler, Gunther (Zootaxa, 2011)
I describe a new species of Anolis related to Anolis (or Norops) altae from Volcán Tenorio, Costa Rica. The new species differs from all other species in the A. altae complex by having the ventral surfaces of body and limbs distinctly reticulated with dark brown pigment and a male dewlap that is dark red with brown blotches, as well as in several morphometric and pholidotic characteristics. It further differs from its geographically nearest congener of this complex, A. monteverde, by having a bilobate hemipenis (unilobate in A. monteverde).